2005
DOI: 10.1002/ajmg.b.30228
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variation in anxiety response to amphetamine: Possible role for adenosine A2A receptor gene variants

Abstract: Amphetamine is thought to produce its stimulant effects mainly via the dopamine system, but its effects may also be influenced by other systems. Dopamine D1 and D2 receptors exist as heterodimers with adenosine A1 and A(2A) receptors, which modulate their responsiveness, suggesting that responses to amphetamine may also depend on adenosinergic function. We therefore studied the relevance of one adenosine A1 and three adenosine A(2A) receptor gene polymorphisms for the interindividual variability in amphetamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

6
4

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…Both rs5751876 C/T and rs35320474 T/− polymorphisms have been associated with increased anxiety after acute administration of amphetamine in healthy subjects (Hohoff et al 2005). The rs5751876 T/T allele has been associated with panic disorder in Caucasian populations (Deckert et al 1998; Hamilton et al 2004), although this association was not replicated in studies in Japanese (Yamada et al 2001) and Chinese subjects (Lam et al 2005).…”
Section: Genetics and Caffeine Responsementioning
confidence: 99%
“…Both rs5751876 C/T and rs35320474 T/− polymorphisms have been associated with increased anxiety after acute administration of amphetamine in healthy subjects (Hohoff et al 2005). The rs5751876 T/T allele has been associated with panic disorder in Caucasian populations (Deckert et al 1998; Hamilton et al 2004), although this association was not replicated in studies in Japanese (Yamada et al 2001) and Chinese subjects (Lam et al 2005).…”
Section: Genetics and Caffeine Responsementioning
confidence: 99%
“…The same polymorphism has been linked to panic disorder (PD) (Deckert et al, 1998;Hamilton et al, 2004), suggesting that this variant confers a risk for anxiety states in general. Recently, we have also reported that individuals with the 1976T/T genotype also experience more anxiety after acute doses of the prototypic stimulant drug, D-amphetamine (Hohoff et al, 2005). As the ADORA2A 1976C/T polymorphism is coding but synonymous (Deckert et al, 1996), it has been suggested that the nearly completely linked rs35320474 (2592T/À) polymorphism, 616 bp downstream of the 1976C/T polymorphism, may alter expression of the A 2A receptor (Alsene et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, first molecular genetic studies investigating the impact of ADORA2A gene variation on anxiety after caffeine intervention demonstrated higher self-reported anxiety levels upon caffeine administration dependent on the ADORA2A 1976T risk allele (Alsene et al, 2003;Childs et al, 2008;Rogers et al, 2010). The ADORA2A 1976 genotype has furthermore been shown to drive subjective and objective responses to caffeine during sleep (Retey et al, 2007) as well as to amphetamines (Hohoff et al, 2005; for review see Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%